The Medieval in the Modern: Command and Consent in Japanese Politics. (October 2016) - Ravina, Mark J.
Modern Japanese political discourse was a syncretic fusion of new Western ideas with medieval and early modern East Asian notions of command and consent. The eleventh-century Chinese concept of 'blocking roads of remonstrance', for example, originally meant that elite imperial advisers should not stop their rivals from addressing the throne. That idea was reworked in nineteenth-centuary Japan as a complement to Western concepts such as 'freedom of speech' and 'consent of the governed.' Political discourse in the 1870s also invoked the medieval sense that a samurai's duty was to his lord's house, rather than to the lord's person. The notion that a retainer could disobey his lord without dishonour was refashioned as a basis for dissent from state edicts in the national interest.